PUSAT PELATIHAN ATLET ESPORTS PROFESIONAL DI CISAUK TANGERANG DENGAN PENERAPAN ARSITEKTUR MODERN - Giga Angger Raditya; Harfa Iskandaria; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Games are increasingly evolving in the present, from the start only in form of entertainment are now also evolved as electronic sports called Esports. Since the 2020 pandemic, game enthusiasts have increased significantly throughout the world and all circles. Likewise in Indonesia, since the pandemic game enthusiasts, especially competitive games, have increased rapidly, this has also made the Esports gaming industry more widely known to the general public. With great enthusiasm from the local community, Esports competitions are now starting to organize competitions both regionally, nationally and internationally. Unfortunately, this sport is relatively new, so the recruitment of Esports athletes is done manually. With the Esports Athlete Training Center in Cisauk Tangerang, it is expected that there will be more professional training place of prospective athletes by having complete data and player performance and making it easier for potential athletes to be recruited to big Esports teams. Besides being a training ground, this area also serves to provide further knowledge for the community about the profession of professional Esports athletes and develop local Esports games. This training area applies modern architecture that adapts to the site and climate in the Cisauk Tangerang area for the convenience of athletes, visitors and management.